The Impact of Electronic Device Use on Students’ Academic Performance and Daily Activities - Zidni Ma’ruf; Ariel Alfachri; Daffa Ramadhan Putra Endito; Mikhael Raja Yudistyra (Chatra: Jurnal Pendidikan dan Pengajaran, 2026)
This study aimed to explore the influence of electronic device use on the academic performance and daily activities of students in the Electrical Engineering Study Program at Politeknik Negeri Sriwijaya. A qualitative descriptive approach was employed involving six students aged 18–22 years who were selected through purposive sampling. Data were collected through semi-structured interviews and group discussions and analyzed using thematic analysis. The findings revealed that electronic devices contributed positively to academic activities by improving access to learning materials, facilitating communication, and supporting students’ understanding of course content. However, participants also reported several challenges associated with prolonged device use, including eye strain, physical fatigue, reduced concentration, technology dependence, and changes in social interaction patterns. Overall, the findings indicate that electronic devices have become integral to students’ academic and daily lives. While these technologies provide substantial educational benefits, their effective use requires balanced and responsible engagement to minimize potential physical, psychological, and social consequences.Penelitian ini bertujuan untuk mengeksplorasi pengaruh penggunaan perangkat elektronik terhadap kinerja akademik dan aktivitas sehari-hari mahasiswa Program Studi Teknik Elektro di Politeknik Negeri Sriwijaya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan melibatkan enam mahasiswa berusia 18–22 tahun yang dipilih melalui teknik purposive sampling. Data dikumpulkan melalui wawancara semi-terstruktur dan diskusi kelompok, kemudian dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa perangkat elektronik memberikan kontribusi positif terhadap aktivitas akademik melalui kemudahan akses terhadap sumber belajar, peningkatan komunikasi akademik, dan dukungan terhadap pemahaman materi perkuliahan. Namun demikian, penggunaan perangkat elektronik secara intensif juga menimbulkan berbagai tantangan, seperti kelelahan mata, kelelahan fisik, penurunan konsentrasi, ketergantungan terhadap teknologi, serta perubahan pola interaksi sosial. Temuan penelitian menunjukkan bahwa perangkat elektronik telah menjadi bagian penting dalam kehidupan akademik dan aktivitas sehari-hari mahasiswa. Oleh karena itu, penggunaan teknologi secara seimbang dan bertanggung jawab diperlukan untuk memaksimalkan manfaat pendidikan sekaligus meminimalkan dampak negatif yang mungkin muncul.